Parenchymal Neurocysticercosis: A Case Study on Diagnostic and Treatment Approach - Thomas, Alina; Fathima, Diya; Ramachandran, Lakshmi; Reji, Kevin (Indian Journal of Pharmacy Practice)
Neurocysticercosis (NCC) is the one of the endemic diseases mostly occurring in Africa, Asia and Latin America making it a major cause of acquired epilepsy in these regions. Transmitted through Taenia solium (the pork tapeworm), contaminated food and water are some of the major sources of infection. Clinical manifestations mostly include seizures, headache and loss of vision and in some cases weakness of extremities. Although a precise incidence of NCC in India is not documented, number of cases has been reported especially in rural areas of the country and among economically backward persons due to unsanitary living conditions. In this case report, we summarize regarding a patient who developed parenchymal Neurocysticercosis after a history of travel that was managed based on guidelines and symptomatic treatment concomitant with supportive care.
Keywords: Neurocysticercosis; T. solium; Epilepsy; Anti-helminthic; Albendazole